THE USE OF INTERACTIVE WHITEBOARDS IN LESSONS OF SCIENCE FROM THE PERSPECTIVE OF PEDAGOGICAL INTERACTION AND COMMUNICATION - MANENOVA, Martina; SVATOS, Tomas (Trends in education, 2012)
It is possible to look at educational communication and interaction from different point of views. The study is aimed at inquiry of communication and interaction among techer and pupils with FIAS method view. Lessons of elementary teachnig at the 1st level of elementary school were the factual subject of inquiry, where teachers use interactive board during lessons.
Keywords: interactive whiteboard; ICT; pedagogical interaction and communication.